Pengaruh senam tera terhadap penurunan tekanan darah pada lansia dengan hipertensi di Posyandu Lansia Kelurahan Pabelan Kartasura - Eriyanti, Mrs. Etty, Arif Widodo, A.Kep.,M.Kes, Arief W. Jadmiko, S.Kep., Ns., M.Kep (2016)
The process of aging is a process that occurs naturally and experience a variety of physical and cognitive deterioration. Physical deterioration that occurs in the elderly, namely deterioration cardiovascular system and cardiovascular diseases common in the elderly is hypertension. Gymnastics tera can improve and enhance the condition and function of the heart and blood circulation, as well as controlling hypertension. The purpose of this study was to determine the effect of gymnastics teradecrease of blood pressure in the elderly with hypertension in the elderly Posyandu Pabelan Kartasura. The study design used is quasy experiment with design time series pretest posttest design. The population is elderly in Posyandu Pabelan Kartasura and met the inclusion criteria. The sample used in this study were 30 elderly people with hypertension. The independent variable in this study is a tera gymnastics, while the dependent variable research is a decrease in blood pressure. Data were analyzed using Wilcoxon signed ranks test to test the hypothesis of comparative two samples are correlated. The results showed that exercise tera effect on systolic blood pressure treatment I, II, II, IV and the diastolic blood pressure I, II, and IV. But gymnastics tera no effect on diastolic treatment III. It is recommended that the elderly can perform calibration exercise regularly to control blood pressure. Keywords: gymnastics tera, decreased blood pressure, elderly